Improvement of NO2 Sensing Properties in Pd Functionalized Reduced Graphene Oxides by Electron-Beam Irradiation - Choi, Myung Sik; Mirzaei, Ali; Bang, Jae Hoon; Oum, Wansik; Kim, Sang Sub; Kim, Hyoun Woo (Frontiers in Materials, 2019)
Considering the great changes in the properties of materials due to electron-beam irradiation (EBI), we present the effect of EBI on the gas-sensing properties of Pd-functionalized reduced graphene oxide (RGO). Scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy were used for the characterization of the synthesized products. The samples were irradiated by electron beams at doses of 100 and 500 kGy and the NO2 gas-sensing properties were investigated. It was found that irradiation by electron beams has a critical effect on the gas-sensing properties of the irradiated samples, with samples irradiated at a dose of 500 kGy showing a higher response relative to that of the 100 kGy irradiated samples. The increased number of high-energy defects was the main cause of the increase in the gas response. Moreover, due to creation of high-energy defects, the response times of sensors irradiated with 500 kGy were decreased by 69.4%. The results of this study can eventually lead to increased performance levels of RGO-based sensors which use EBI, as this technology can introduce changes in materials in a non-contact, clean and powerful manner.